2020
DOI: 10.3390/ijerph17207510
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Changes, Spatiotemporal Differences and Factors Influencing the Urban Eco-Efficiency in the Lower Reaches of the Yellow River

Abstract: The measurement of eco-efficiency is an important tool to evaluate the level of urban sustainable development. Therefore; improving urban eco-efficiency in the lower reaches of the Yellow River ensures the implementation of ecological protection and high-quality development strategies in the Yellow River Basin. In this study; the dynamic changes of urban eco-efficiency and spatiotemporal differences in the lower reaches of the Yellow River were investigated using the Super-SBM (Super-Slack measure model) model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 62 publications
0
8
0
Order By: Relevance
“…Since then, Tone also proposed a Super-SBM model in conjunction with the super-efficiency DEA model, which remedies the shortcoming of the SBM model that cannot achieve a complete ranking of DMUs [ 34 ]. Recently, some scholars have used the improved Super-SBM DEA method to measure the ecological efficiency of regions [ 35 , 36 ]. However, undesirable outputs are not considered in most of the articles.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Since then, Tone also proposed a Super-SBM model in conjunction with the super-efficiency DEA model, which remedies the shortcoming of the SBM model that cannot achieve a complete ranking of DMUs [ 34 ]. Recently, some scholars have used the improved Super-SBM DEA method to measure the ecological efficiency of regions [ 35 , 36 ]. However, undesirable outputs are not considered in most of the articles.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The DEA method and Malmquist index model measure the efficiency of the DMUs, and the two methods do not obtain the key factors affecting the DMUs [ 20 , 35 ]. Therefore, to make more targeted recommendations and suggestions with guidance for the DMUs, an effective influence factor analysis method is needed for analysis.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the existing research, economic development [70], green technology [70], industry structure [71], population or labor force [42,72], capital [30,31,72], and environmental regulation [73] were the main influencing factors for improving the regional eco-efficiency or green and sustainable development. Therefore, this article referenced existing research [74][75][76] and incorporated the below indicators in the panel Tobit regression model to analyze the influencing factors of eco-efficiency in Mongolia.…”
Section: The Influencing Factors Of Eco-efficiency In Mongoliamentioning
confidence: 99%
“…On the city scale, Ren et al (2020) applied the Hybrid distance model (S-EBM) to measure the eco-efficiency of 283 prefecture-level cities in China from 2003 to 2013 and found that an increase in eco-efficiency in surrounding cities would improve eco-efficiency in local cities [29]. Zhang et al (2020) analyzed the regional eco-efficiency of cities along the lower reaches of the Yellow River from 2007 to 2018 using the super SBM model and found that affluence and technological progress were the main drivers of eco-efficiency [30]. Yao et al (2021) used the epsilon-based measure data envelopment analysis (EBM-DEA) model to analyze the regional eco-efficiency of 28 Russian cities along the Northern Sea Route and found that the cities with higher levels of GRPs per capita had higher eco-efficiency [31].…”
Section: Introductionmentioning
confidence: 99%
“…As an essential factor in production and life, water resource utilization efficiency has been a hot topic in academia. Improving water use efficiency is the primary way to sustain water resources [ 1 , 2 ]. An efficient and accurate evaluation method depends on water resource utilization and efficiency evaluation.…”
Section: Introductionmentioning
confidence: 99%